Assessing the Adoption of Climate Resilient Agricultural Technologies by the Farmers of Telangana State (Indian Journal of Extension Education, 2022)
In agriculture sector, the effect of climate change seems to have become inevitable during the last few decades. Hence, the technologies for climate-resilient agriculture (CRA) are probably the best adaptation solutions currently available to improve the resilience of agriculture. The study to access the extent of adoption of CRA technologies by the farmers in the National Innovations in Climate Resilient Agriculture (NICRA) project implemented villages of Suryapet and Khammam districts in Telangana state was conducted during 2021-22. Total 200 farmers from these two districts were selected randomly to evaluate the adoption status of recommended CRA technologies and its association with the respondents’ profile characteristics. The respondents had adopted CRA technologies at medium to high levels with the majority of beneficiaries adopting technologies like deep ploughing, in-situ moisture conservation technologies in cotton and red gram, crop diversification from paddy to jowar and vegetables as a contingent crop, improved variety of paddy Siddhi WGL-44 and improved backyard poultry breeds. The profile characteristics viz., education, annual income, land holding, individual and mass media exposure, economic motivation, risk-taking ability, and innovative proneness had a positive and significant association with the extent of adoption of CRA technologies.